Ultra-high efficient novel plasma aluminum-nitriding methodology and performances analysis. (November 2022) - Kang, Qianfei; Wei, Kunxia; Fan, Haomin; Liu, Xilang; Hu, Jing
Abstract: A novel plasma aluminum-nitriding technology was primarily developed by depositing an aluminum hydroxide film on the surface of 42CrMo samples through electrolyzing aluminum nitrate prior to plasma nitriding at 520 ℃ for 4 h. Excellent performances were obtained by the novel plasma aluminum-nitriding technology. The process efficiency was remarkably enhanced comparing with traditional plasma nitriding, with the thickness of compound layer and effective hardening layer increasing from 17.24 μm to 52.13 μm, and 175 μm to 1050 μm, respectively. More importantly, the performances were dramatically promoted due to the formation of mixture compounds of Fex N, AlN and Fex Al, with the surface hardness increasing from 750 HV0.025 to 1250 HV0.025, wear rate decreasing from 3.22×10 –5 g·m –1 ·N –1 to 1.21×10 –5 g·m –1 ·N –1, and corrosion rate decreasing from 5.42 μm/a to 1.23 μm/a. Therefore, the research can provide wonderful insights into the surface modification technology. Graphical abstract: A novel plasma aluminum-nitriding technology was primarily developed by depositing an aluminum hydroxide film on the surface of 42CrMo samples through electrolyzing aluminum nitrate prior to plasma nitriding at 520 ℃ for 4 h. Excellent performances were obtained by the novel plasma aluminum-nitriding technology. The process efficiency was remarkably enhanced comparing with traditional plasma nitriding, with the thickness of compound layer and effective hardening layer increasing from 17.24 μm to 52.13 μm, and 175 μm to 1050 μm, respectively. More importantly, the performances were dramatically promoted due to the formation of mixture compounds of Fex N, AlN and Fex Al, with the surface hardness increasing from 750 HV0.025 to 1250 HV0.025, wear rate decreasing from 3.22×10 –5 g·m –1 ·N –1 to 1.21×10 –5 g·m –1 ·N –1, and corrosion rate decreasing from 5.42 μm/a to 1.23 μm/a. Therefore, the research can provide wonderful insights into the surface modification technology. Image, graphical abstract